Integrated analysis of metabolome and transcriptome reveals the cytoplasmic effects of CMS-D2 on pollen fertility resulting from disrupted lipid metabolism - Zhang, Xuexian; Zhang, Meng; Guo, Liping; Qi, Tingxiang; Tang, Huini; Li, Yongqi; Zuo, Zhidan; Shahzad, Kashif; Feng, Juanjuan; Zang, Rong; Wang, Hailin; Qiao, Xiuqin; et al. (Frontiers in Plant Science, 2022)
Using cytoplasmic male sterility of G. harknessii (CMS-D2) is an economical and effective method to produce cotton hybrids. However, the detrimental cytoplasmic effects of CMS-D2 on pollen fertility and fiber yields greatly limit the further development of three-line hybrid cotton in China. In this study, an integrated non-targeted metabolomics and transcriptome analysis was performed on mature pollens of maintainer line NB, isonuclear alloplasmic near-isogenic restorer lines NH and SH under two environments. A total of 820 metabolites were obtained, of which lipids and lipid-like molecules were the most, followed by organic acids derivatives, phenylpropanoids, and polyketides. Transcriptome analysis revealed significantly more differentially expressed genes (DEGs) in SH versus NH both in Anyang and Jiujiang, and most of the DEGs were significantly up-regulated. Further KEGG analysis showed that most DEGs were enriched in the biosynthesis of unsaturated fatty acids, phenylalanine metabolism, and phagosome. Based on the weighted gene co-expression network analysis, totally 74 hub genes were also identified, of which three transcription factors, i.e., WRKY22, WRKY53, and ARF18 were significantly up-regulated in SH and may play a negative regulatory role in pollen development by directly or indirectly regulating the jasmonic acid synthesis and signal transduction. Moreover, we found that the negative effects of CMS-D2 cytoplasm on pollen fertility were mainly due to disturbed lipid metabolism, especially the metabolic balance of unsaturated fatty acids, ultimately resulting in the decline of pollen fertility. Meanwhile, in the presence of CMS-D2 sterile cytoplasm, the cytoplasmic-nucleus interaction effects generated a substantial quantity of flavonoids involved in the fertility restoration process. This study preliminarily clarified some of the reasons for the negative effects of CMS-D2 cytoplasm on pollen fertility, and our results will provide an important theoreti